2020
DOI: 10.18502/jmehm.v13i19.4827
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal end-of-life decisions and ethical perspectives

Abstract: End-of-life decisions are usually required when a neonate is at high risk of disability or death, and such decisions involve many legal and ethical challenges. This article reviewed the processes of ethical decision-making for severely ill or terminal neonates, considering controversial issues including the followings: (i) identifying primary decision makers, (ii) the role of law and guidelines, and (iii) changes in treatment controversy, law and regulations over twenty years in several European countries such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It is reported that greater effort is needed to actively implement palliative care and promote palliative care practices across health disciplines 12,14 . Neonatal nurses, physicians, and families must cooperate in providing palliative care, and end-of-life care practices and support for grieving parents after an infant's death should be planned with multidisciplinary collaboration 11,16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that greater effort is needed to actively implement palliative care and promote palliative care practices across health disciplines 12,14 . Neonatal nurses, physicians, and families must cooperate in providing palliative care, and end-of-life care practices and support for grieving parents after an infant's death should be planned with multidisciplinary collaboration 11,16 …”
Section: Introductionmentioning
confidence: 99%
“…12,14 Neonatal nurses, physicians, and families must cooperate in providing palliative care, and end-of-life care practices and support for grieving parents after an infant's death should be planned with multidisciplinary collaboration. 11,16 Health professionals dealing with neonatal palliative care often experience emotional stress and ethical dilemmas that can adversely affect their attitudes toward end-of-life care. 17,18 Health care professionals caring for infants with terminal illness can experience the same emotions experienced by the infant's family, including anxiety, fear, guilt, anger, and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal palliative care involves complex ethical and legal considerations, including issues related to decision-making about treatment and withdrawal of care, end-of-life care, bereavement support, and parental autonomy. Integrating these services into the healthcare system enables the establishment of ethical guidelines, protocols, and legislative frameworks that ensure that the best interests of neonates and their families are prioritized [ 16 ]. By incorporating neonatal palliative care into the Greek national healthcare system, end-of-life decision-making informed consent, and the reporting of certain conditions or circumstances, depending on the jurisdiction, will be strictly adhered to confidentiality, privacy, and laws, thus promoting a respectful and evidence-based approach.…”
Section: Editorialmentioning
confidence: 99%